The Role of Remuneration in Improving the Quality of Public Services in Indonesia - Kurhayadi (Global Writing Academica Researching & Publishing, 2020)
To improve the quality of social life in the community, it is necessary to have good public services. Therefore, if the existing public services are of poor quality, the public’s trust in the bureaucracy will be even worse. Good public services can be provided if government employees who work in public services work well. This study then aims to see how the role of remuneration on the quality of public services that occur in Indonesia. This research will be carried out using a qualitative approach the method. The results of this study found that the provision of commensurate remuneration can improve the quality of public services. This is because the provision of remuneration will create commitment for employees in carrying out their duties properly, so that the public services that can be provided also have good quality. This will then create good governance and clean government.